If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(5x + -2) = -3 Reorder the terms: x(-2 + 5x) = -3 (-2 * x + 5x * x) = -3 (-2x + 5x2) = -3 Solving -2x + 5x2 = -3 Solving for variable 'x'. Reorder the terms: 3 + -2x + 5x2 = -3 + 3 Combine like terms: -3 + 3 = 0 3 + -2x + 5x2 = 0 Begin completing the square. Divide all terms by 5 the coefficient of the squared term: Divide each side by '5'. 0.6 + -0.4x + x2 = 0 Move the constant term to the right: Add '-0.6' to each side of the equation. 0.6 + -0.4x + -0.6 + x2 = 0 + -0.6 Reorder the terms: 0.6 + -0.6 + -0.4x + x2 = 0 + -0.6 Combine like terms: 0.6 + -0.6 = 0.0 0.0 + -0.4x + x2 = 0 + -0.6 -0.4x + x2 = 0 + -0.6 Combine like terms: 0 + -0.6 = -0.6 -0.4x + x2 = -0.6 The x term is -0.4x. Take half its coefficient (-0.2). Square it (0.04) and add it to both sides. Add '0.04' to each side of the equation. -0.4x + 0.04 + x2 = -0.6 + 0.04 Reorder the terms: 0.04 + -0.4x + x2 = -0.6 + 0.04 Combine like terms: -0.6 + 0.04 = -0.56 0.04 + -0.4x + x2 = -0.56 Factor a perfect square on the left side: (x + -0.2)(x + -0.2) = -0.56 Can't calculate square root of the right side. The solution to this equation could not be determined.
| x(5x-2)=3 | | 5x+6=23 | | 3x=2x+25 | | 3.3x=2.2x+5.5 | | x/(-2)=7 | | -8t=34 | | (c^3+2c^2d+cd^2)=0 | | X-8=40 | | 13-x=-3 | | 5-4x+5x=6x-12 | | z+1=-17 | | 4x^2+2x+7=0 | | 0.3x+0.4(10)=0.2(x+20) | | x-54=-7 | | 4x=s+5x | | x/10+2=18 | | 2x=5x-3y | | 2(3.14)=5x-3y | | 5.8+1.3n=2.29 | | (y-1)+y=11 | | 6x^2+6x+6=14x+14 | | 1x-9=14 | | -(68c+38d+8)= | | -6x-y+3xy=18 | | x^2-3.5X+3.0625=1.0625 | | -6x-y+3xy-18=0 | | 3d+4=2+3d+0.5 | | 7x-(4x+2)= | | 2a+6=3 | | 22=2x-8 | | 6-3(6)= | | w-6-12=-8 |